ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEHANDALAN SISTEM PROTEKSI KEBAKARAN PADA BANGUNAN GEDUNG NEGARA DI KOTA MATARAM - Roziana, B. Hurul Ismi; Murtiadi, Suryawan; Akmaluddin, Akmaluddin (Teknisia, 2015)
State Buildings are the state assets that have strategic value as a place to process the state administration and serve the public service activities, health and education. Fire in the buildings can cause problems and threats due to a variety of unintended consequences such as loss of life, destruction of buildings, loss of data and other assets that are stored in the buildings. Therefore, the aim of this research is to investigate the relationship between material usage, building designs, detection and fire alarm system, fire extinguishers, fire hydrants and sprinklers, and the reliability of fire protection system of the state buildings in Mataram. A descriptive research method was used in this study. Sixty building sample consisted of 30 simple buildings and 30 non-simple buildings, built from 2009 to 2014, were considered. Samples data obtained were processed using SPSS 18.0 software. The results showed that 91.1% of the fire protection reliability on the state buildings affected by 6 independent variables, namely usage of materials (X1), building design (X2), detection and fire alarm system (X3), fire extinguishers (X4), fire hydrant (X5) and sprinklers (X6). The six independent variables have a significant effect simultaneously showed by F value of 90.339 higher than F table of 2.3966 with a significance value less than 0.05. From the six independent variables only 4 variables have partially significant influence on the fire protection reliability of the state buildings in Mataram that was X1, X2, X3 and X4. This showed by the value of the variables t test were higher than t table of 2.0066 with the significance less than 0.05. Thus, X5 and X6 did not have any partially significant effect on the fire protection reliability of the state buildings in Mataram.